Example of best practice: refugee teachers at the University of Potsdam. A requalification program for newly arrived teachers in Germany. Issue 1 (2nd January 2021) - Niesta Kayser, Daniela; Vock, Miriam; Wojciechowicz, Anna Aleksandra
ABSTRACT: The Refugee Teachers Program, established at the University of Potsdam, Brandenburg, in 2016, represents a successful model for training and integrating individuals with foreign teaching qualifications through an 18-month teaching and language course. Initially created to help meet the demand for teachers in Germany, the Refugee Teachers Program has been further refined over the course of the last three years in the light of expert meetings, theoretical considerations, and negotiations with the Brandenburg Ministry of Education. This was the first program of its kind in Germany, following an influx of people being forced to migrate from countries such as Syria, Afghanistan, and Iraq in 2015. The program responded to these international events by providing training, work, and refuge for migrants who already had teaching experience in their home countries. More than 85 participants successfully completed the program and many have taken up newly created positions as teachers and pedagogical assistants in German schools. However, a number of hurdles still remain before most of the program's graduates can be granted full employment as teachers in Germany.